2021
DOI: 10.1007/s12035-021-02418-6
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Skin Prion-Seeding Activity of Prion-Infected Mice Treated with a Compound Against Human and Animal Prions: a First Possible Biomarker for Prion Therapeutics

Abstract: Previous studies have revealed that the infectious scrapie isoform of prion protein (PrPSc) harbored in the skin tissue of patients or animals with prion diseases can be amplified and detected through the serial protein misfolding cyclic amplification (sPMCA) or real-time quaking-induced conversion (RT-QuIC) assays. These findings suggest that skin PrPSc-seeding activity may serve as a biomarker for the diagnosis of prion diseases; however, its utility as a biomarker for prion therapeutics remains largely unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…While the RT-QuIC represents one of the major breakthroughs for the antemortem diagnosis of these diseases, it does not provide specific information about the prion strain, thus hampering the possibility to recognize sCJD subtypes and stratify patients when they are alive. This aspect is of fundamental importance since a strain-dependent efficacy of anti-prion compounds has been emerging (Barret et al, 2003;Yung et al, 2004;Cronier et al, 2007;Berry et al, 2013;Ding et al, 2021). In this work, we have evaluated the efficiency of an optimized PMCA to faithfully amplify prion strains across the spectrum of sCJD subtypes using OM samples collected from living patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the RT-QuIC represents one of the major breakthroughs for the antemortem diagnosis of these diseases, it does not provide specific information about the prion strain, thus hampering the possibility to recognize sCJD subtypes and stratify patients when they are alive. This aspect is of fundamental importance since a strain-dependent efficacy of anti-prion compounds has been emerging (Barret et al, 2003;Yung et al, 2004;Cronier et al, 2007;Berry et al, 2013;Ding et al, 2021). In this work, we have evaluated the efficiency of an optimized PMCA to faithfully amplify prion strains across the spectrum of sCJD subtypes using OM samples collected from living patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile to use innovative and rationale approaches to investigate FDA-approved compounds for repurposing to expedite the development of novel and safe therapeutics to treat AD. Recently, we and other groups tested FDA-approved CEs in prion diseases and found that CEs have therapeutic effects by inhibiting propagation of prions, infectious agents generated upon misfolding of the host's cellular prion protein and prototypic for other misfolded proteins associated with neurodegenerative diseases, and extend the survival of prion-infected mice [30][31][32][33][34][35]. Herein, we tested and validated for the first time FDA-approved CE (HPMC) representative TC-5RW (Type E (Hypromellose 2910 classified by the United States Pharmacopeia)) as a potential, emerging and effective compound to halt and treat familial AD.…”
Section: Discussionmentioning
confidence: 99%
“…The US Food and Drug Administration (FDA) approved HPMC as a safe pharmaceutical and food additive and reported that quantities up to 670 mg in oral formulations are safe to humans [27][28][29]. However, recently our and other groups' studies showed that CEs have therapeutic effects in neurodegenerative diseases via inhibiting the propagation of prions, infectious agents consisting of a misfolded protein [30][31][32][33][34][35]. Most importantly, subcutaneous (SC) administration of CEs even one year prior to prion infection significantly increased the life span of prion-infected mice [31].…”
Section: Introductionmentioning
confidence: 99%
“…When considering quantification of seeding activity as a pharmacodynamic biomarker, inhibition of the RT-QuIC assay due to direct inhibition of in vitro seeding by anti-aggregation agents complicates interpretation, although estimation of drug concentration in the sample and comparing its inhibitory effect on the RT-QuIC of samples with known seeding activity may aid interpretation (Ding et al, 2021 ). Another complexity of interpretation of RT-QuIC in trials of anti-aggregation agents to consider, particularly in the context of treatment failure, is whether the emergence of a drug-resistant protein strain would be detectable or not, due to potential alteration in RT-QuIC amyloid seeding activity.…”
Section: Role Of Protein Aggregation With Seed Amplification Assays I...mentioning
confidence: 99%
“…A potential limitation is the patient tolerability of serial lumbar puncture during the clinical trial, although seed amplification assays have been applied to other more accessible analytes. Interestingly in a mouse model of prion disease skin RT-QuIC seeding activity was abolished by treatment with an anti-prion agent that prolonged survival, suggesting a potential role for skin RT-QuIC as a pharmacodynamic biomarker (Ding et al, 2021 ). However, despite the ease of skin biopsy relative to lumbar puncture, CSF remains a more attractive analyte for assessing drug target engagement in the central nervous system owing to its proximity to the brain parenchyma.…”
Section: Role Of Protein Aggregation With Seed Amplification Assays I...mentioning
confidence: 99%